2021
DOI: 10.1007/s00266-021-02140-7
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Versus Placebo: A Meta-Analysis of Treatment and Quality-of-life Outcomes for Hyperhidrosis

Abstract: Aims This study aims at assessing the treatment effect, disease severity and quality-of-life outcomes of botulinum toxin (BTX) injections for focal hyperhidrosis. Methods We included randomized controlled trials of BTX injections compared with placebo for patients with primary or secondary focal hyperhidrosis. PubMed, Embase and the Cochrane Library were searched to August 2020. Gravimetric sweat rate reduction, disease severity measured by Hyperhidrosis D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
1
6
0
9
Order By: Relevance
“…16 In another trial about BTX-A, only one patient developed increased facial sweating after axillary hyperhidrosis. 17 On the other hand, a small observational prospective study found that there is no evidence of CH as measured by evapometry in patients diagnosed with palmar hyperhidrosis treated with botulinum toxin A, Although two of their 17 patients (11%) had reported subjective CH. 18 On the contrary, CH after surgical sympathectomy is thoroughly studied in the literature, but the pathogenesis and risk factors are still not well explained.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…16 In another trial about BTX-A, only one patient developed increased facial sweating after axillary hyperhidrosis. 17 On the other hand, a small observational prospective study found that there is no evidence of CH as measured by evapometry in patients diagnosed with palmar hyperhidrosis treated with botulinum toxin A, Although two of their 17 patients (11%) had reported subjective CH. 18 On the contrary, CH after surgical sympathectomy is thoroughly studied in the literature, but the pathogenesis and risk factors are still not well explained.…”
Section: Discussionmentioning
confidence: 97%
“…A clinical trial that aimed to investigate the safety and efficacy of BTX-A in axillary hyperhidrosis mentioned that only 11 patients (5%) developed CH. 16 In another trial about BTX-A, only one patient developed increased facial sweating after axillary hyperhidrosis. 17 On the other hand, a small observational prospective study found that there is no evidence of CH as measured by evapometry in patients diagnosed with palmar hyperhidrosis treated with botulinum toxin A, Although two of their 17 patients (11%) had reported subjective CH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os dados de notificação registrados no SINAN, no período entre 2011 e 2018, no estado do Espírito Santo, revelam que cerca de sete em cada dez casos de violência contra a pessoa com deficiência apresentavam caráter de repetição. Esse resultado é superior ao encontrado em grupos também vulneráveis como as crianças (P: 32,5%) (PEDROSO; LEITE, 2021) e pessoas idosas (P: 50,1%) (PAMPOLIM; LEITE (2021), demonstrando o quanto as pessoas com deficiência estão entre aqueles mais vulneráveis à permanência do ciclo da violência.…”
Section: Discussionunclassified
“…These studies showed statistically significant improvement in overall DLQI mean score reduction from baseline to 2-8 week posttreatment, with a reported at least a 2-grade improvement in the HDSS. 97 Onabotulinum toxin A also has reported improvement in quality-of-life outcomes for nondermatologic conditions, such as poststroke lower limb spasticity, cervical dystonia, and masseter muscle hypertrophy. [98][99][100] 8 | SAFETY PROFILE…”
Section: Immunogenicity and Neutralizing Antibodiesmentioning
confidence: 99%